Targeted therapy of esophageal squamous cell carcinoma: the NRF2 signaling pathway as target. Issue 1 (11th May 2018) - Ma, Shaohua; Paiboonrungruan, Chorlada; Yan, Tiansheng; Williams, Kevin P.; Major, M. Ben; Chen, Xiaoxin Luke
Abstract: Esophageal squamous cell carcinoma (ESCC) is a deadly disease that requires extensive research. Here, we review the current understanding of the functions of the nuclear factor erythroid‐derived 2–like 2 (NRF2) signaling pathway in the esophagus. Genomic data suggest that gene mutations and several other mechanisms result in NRF2 hyperactivation in human ESCC. As a consequence, NRF2 high ESCC is more resistant to chemoradiotherapy and associated with poorer survival than NRF2 low ESCC. Mechanistically, we believe NRF2, functioning as a transcription factor, causes an esophageal phenotype through regulation of gene transcription. We discuss metabolism, mitochondria, proteasomes, and several signaling pathways as downstream players that may contribute to an esophageal phenotype due to NRF2 hyperactivation. Finally, strategies are proposed to target the NRF2 signaling pathway for therapy of NRF2 high ESCC. Abstract : Genomic data suggest that gene mutations and several other mechanisms result in NRF2 hyperactivation in human esophageal squamous cell carcinoma (ESCC). As a consequence, NRF2 high ESCC is more resistant to chemoradiotherapy and has poorer survival than NRF2 low ESCC. We discuss metabolism, mitochondria, proteasomes, and other signaling pathways as downstream players that may contribute to phenotypes due to NRF2 hyperactivation